Rapid Decrease in Rates of Hospitalization Resulting From Invasive Pneumococcal Disease and Community-Acquired Pneumonia in Children Aged <60 Months After 13-Valent Pneumococcal Conjugate Vaccine Introduction in Argentina. (23rd February 2017) - López, Eduardo L; Glatstein, Eduardo; Ezcurra, Gustavo C; Iacono, Marisa; Teplitz, Eduardo; Garnero, Analía V; Lazzarini, Daniela L; Vázquez, Miryan; Contrini, María M
Abstract: Background: In January 2012, Argentina included universal pneumococcal vaccination in the routine childhood vaccination program using a 13-valent pneumococcal conjugate vaccine (PCV13). A 2 + 1 schedule (2 doses in the first year of life and a booster dose at 12 months of age) in children aged <2 years and 2-dose catch-up immunization in children aged 13 to 24 months was administered during the first year of vaccine introduction. The purpose of this study was to assess the burdens of invasive pneumococcal disease (IPD) and/or community-acquired pneumonia (CAP) in hospitalized children younger than 5 years during the first 2 years of the program compared to those in the prevaccination period in our setting. Methods: This was a multicenter, prospective, and descriptive study. Rates of hospitalization resulting from IPD and/or CAP in 5 pediatric reference centers across the country were analyzed (every 10 000 admissions). Clinical, epidemiologic, and microbiological data were recorded. Statistical analysis using Stata 8.0 was performed. Results: A comparison of rates of hospitalization resulting from global IPD and/or CAP in the prevaccine (2009–2011) and postvaccine (2012–2013) periods revealed significant decreases of 50% ( P = .003) and 51% ( P < .0001), respectively. Significant decreases were also observed in number of hospitalizations resulting from empyema (39%; P = .03) and pneumococcal empyema (67.8%; P = .007); the reduction was not statistically significant for pneumococcal CAP (58%; P = .18). Hospital stays for IPD and/or CAP decreased by 56%. Conclusion: Rapid and significant decreases in the rates of hospitalization resulting from IPD and/or CAP during the first 2 years after PCV13 introduction were observed. A longer surveillance period is required to confirm these results and the effectiveness of the vaccination program.